2018
DOI: 10.12659/msm.907955
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging in Diagnosis of Post-Traumatic Syringomyelia in Spinal Cord Injury in Rats

Abstract: BackgroundPost-traumatic syringomyelia (PTS) is a common disease after spinal cord injury (SCI). The present study was performed to evaluate the advantages of diffusion tensor imaging (DTI) in estimating SCI and prognosing PTS in SCI rats.Material/MethodsForty rats were divided into 3 groups based on the extent of the individual SCI and PTS: a control group (n=10), a PTS group (n=8), and an SCI group (n=22). BBB tests were performed preoperatively and postoperatively at (1 d, 3 d, 5 d, 1 w, 2 w, 1 w, 2 w, 3 w,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Many quantitative magnetic resonance (qMRI) techniques have been used to study the spinal cord (Lommers et al, 2021 ; Savini et al, 2021 ), and diffusion tensor imaging (DTI) is one of the most commonly used research methods (McLachlin et al, 2021 ). DTI is a standard neuroscience technique that is more sensitive than conventional MRI in evaluating spinal cord injuries (Zhang et al, 2018 ), and it provides important information about structural integrity, including myelin formation, axon diameter, and fiber density (Kumar et al, 2021 ), which indirectly reflect the degree of degeneration and pathophysiological structural changes of the spinal cord in vivo . Previous studies found that conventional MRI did not show any abnormalities in the spinal cord, but DTI revealed reduced fractional anisotropy (FA) and increased apparent diffusion coefficient (ADC) values in these patients, which indicated potential injury to the spinal cord (Lee et al, 2015 ; Shabani et al, 2020 ; Singh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many quantitative magnetic resonance (qMRI) techniques have been used to study the spinal cord (Lommers et al, 2021 ; Savini et al, 2021 ), and diffusion tensor imaging (DTI) is one of the most commonly used research methods (McLachlin et al, 2021 ). DTI is a standard neuroscience technique that is more sensitive than conventional MRI in evaluating spinal cord injuries (Zhang et al, 2018 ), and it provides important information about structural integrity, including myelin formation, axon diameter, and fiber density (Kumar et al, 2021 ), which indirectly reflect the degree of degeneration and pathophysiological structural changes of the spinal cord in vivo . Previous studies found that conventional MRI did not show any abnormalities in the spinal cord, but DTI revealed reduced fractional anisotropy (FA) and increased apparent diffusion coefficient (ADC) values in these patients, which indicated potential injury to the spinal cord (Lee et al, 2015 ; Shabani et al, 2020 ; Singh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in some patients without clinical symptoms, the microstructural function of the spinal cord at the cavity may have been seriously disturbed, which requires timely intervention and treatment. DTI may be used in syringomyelia to investigate microstructural changes in spinal fibre tracts around and beyond the syrinx, which are not available in conventional MRI and other technologies 10,11,14 . Currently, few studies have reported the application of DTI technology in patients with syringomyelia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the authors concluded that the FA parameter might be a better DTI parameter to evaluate the microstructural damage of the spinal cord. In an animal study of spinal cavity after spinal cord trauma, Zhang et al 14 found that the FA values were significantly decreased and the ADC values were significantly increased after spinal cord injury. However, following repair of the spinal cord injury, even if a spinal cavity appeared, the FA values increased notably; additionally, there was no obvious change in the ADC values.…”
Section: Discussionmentioning
confidence: 99%
“…As an incidental finding, a Th2/3 fracture occurred at the site of the hemangioma. c, d Following contrast enhancement, an underlying pathology could be excluded a standardized experimental impact injury at the level of Th 9/10, 27% of rats develop a PTS within 6 weeks [18]. Symptomatic PTS may occur in less than 10% of patients with SCI, while the prevalence of an asymptomatic syrinx in patients who have been followed for 30 years is approximately 28% [19,20].…”
Section: Degree Of Spinal Injury and Development Of Syringomyeliamentioning
confidence: 99%